A Theoretical Literature Review on Adaptive Structuration Theory as Its Relevance to Human Resource Development. Issue 3 (August 2019) - Turner, John R.; Morris, Mark; Atamenwan, Imonitie
The Problem: Adaptive structuration theory (AST) has had little to no attention within the human resource development (HRD) literature. It is important for HRD scholars and scholar-practitioners to be concerned with how new technology initiatives impact both the individual and the organization, equally. Unfortunately, new technologies are often introduced with no consideration of its utility to the agents expected to use these new technologies, causing incompatibilities and productivity losses. The Solution: AST views the duality of structure between an organization's structural features and its human agents. This perspective enables human agents when implementing new technologies and organizational change initiatives. Also, AST provides HRD scholars and scholar-practitioners with new insight into the interactions that take place during these change initiatives, providing support for current and future research efforts. The Stakeholders: It would be beneficial for HRD scholars and scholar-practitioners involved with designing, evaluating, implementing, or managing technology in the workplace.